EFFECT OF CRUDE PALM OIL (CPO) PROTECTED BY FORMALDEHYDE ON PHYSICAL AND CHEMICAL QUALITY OF LAMB - Tiven, N.C.; Yusiati, L. M.; Rusman, R.; Santoso, U. (Diponegoro University, 2015)
This study was conducted to determine the effect of crude palm oil (CPO) protected byformaldehyde on chemical and physical quality of lamb. The research design applied was completelyrandomized design with 3 treatments and 5 replications Fifteen local male sheeps aged 9-12 monthsweighing 14-17 kg were divided into 3 groups for different ration treatments. The first group receivedonly basal ration (R0), the 2nd group received basal ration and 3% of CPO (R1), while the 3rd groupreceived basal ration and 3% of CPO protected by 2% of formaldehyde (R2). The data were analyzed byanalysis of variance. The differences among treatments were tested by Duncan’s New Multiple RangeTest. The results showed that the addition of CPO protected by formaldehyde (R2) in the sheep dietincreased lamb protein and fat content (P<0.05), produced tenderer lamb (P<0.01) with lower cookingloss (P<0.01). The diet with CPO protected by formaldehyde can improve the chemical and physicalquality of meat sheeps.